A decentralized proportional-integral sliding mode tracking controller for robot manipulators - Ahmad, Mohamad Noh; Osman, Johari Halim Shah; A. Ghani, Mohd. Ruddin (2002)
This paper presents a decentralized Proportional-Integral (PI) sliding mode tracking control for a class of robot manipulators. A robust decentralized sliding mode controller is derived so that in each of the sub-system, the actual trajectory tracks the desired trajectory using the information available only on the local states. The PI sliding mode is chosen to ensure the stability of overall dynamics during the entire period i.e. the reaching phase and the sliding phase. It is shown theoretically and by simulation that manipulator systems controlled by the proposed decentralized control law are practically stable.